Transposon Insertion Phenomenon during Cloning of a Partial Fragment Derived from Metagenomic DNA Isolated from Deep-Sea Water and Sediment of Kawio Island, North Sulawesi - Agung, Mochamad Untung Kurnia; Moeis, Maelita Ramdani (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Transposon is well-known as mobile element found abundant both in prokaryote and eukaryote genomes. In bacteria, transposon (famous name of a transposable DNA) could jump from chromosome to plasmid and its contrary. One type of transposons in bacteria known as insertion sequence (IS), it does not contain any additional genes except a gene encoding transposase, an enzyme that correlated to transponsition activities. The finding of transposon insertion unfortunately found during cloning of a fragment derived from deep-sea metagenomic DNA in this research. In the initial, this research was aimed to clone and characterize the Ã¡-amylase encoded gene derived from metagenomic DNA isolated from deep-sea water and sediment of Kawio Island, North Sulawesi. Metagenomic DNA has been isolated from deep-sea water and sediment and by using Whole Genome Amplification (WGA) technique, the DNA it could be increased in quantities to 146,31 ng for each 1 ng of metagenomic DNA. A fragment of 1000 bp in length was obtained by using touchdown PCR method. The presence of a transposon in this DNA fragment is proposed as a hypothesis for losing 700 bp leaving just 310 bp cloned sequence. Analysis of sequencing result showed a highest similarity between this 310 bp partial fragment with a replication protein (Rep) encoded gene from Pseudomonas putida (Query Coverage: 88%; Max. Identity: 80%, Positive: 86%) and this protein is known to be involved in plasmid replication where transposase encoding genes known usually presence together with this gene (Rep gene) in a bacterial plasmid.